2019
DOI: 10.1002/pmrj.12055
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Subacromial Pain Syndrome Present no Reduction of Shoulder Proprioception: A Matched Case‐Control Study

Abstract: Background Shoulder pain is common among patients with musculoskeletal pain and the prevalence of patients with subacromial pain syndrome (SAPS) is high. Despite the high prevalence, there is a lack of an extensive evaluation of the proprioception acuity in patients with SAPS. Knowledge of the proprioceptive deficit would assist clinicians in the proper treatment and may offer an alternative explanation for the mechanisms underlying SAPS, which are poorly understood. Objective To compare the proprioceptive fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 28 publications
0
8
0
1
Order By: Relevance
“…The risk of bias in this study was low, and a reliability assessment showed that measurements were performed with good reliability during testing in 40 and moderate reliability during testing in 100 (Table 2) [16]. During both passive and active axial humerus rotation testing neither of the two studies found a difference in MM degree between patients with SAPS and controls [18,34]. Thus, Joint Position Sense in patients with SAPS may be affected during high scaption [16], but seems to be preserved during axial humerus rotation [18,34].…”
Section: Joint Position Sensementioning
confidence: 61%
See 3 more Smart Citations
“…The risk of bias in this study was low, and a reliability assessment showed that measurements were performed with good reliability during testing in 40 and moderate reliability during testing in 100 (Table 2) [16]. During both passive and active axial humerus rotation testing neither of the two studies found a difference in MM degree between patients with SAPS and controls [18,34]. Thus, Joint Position Sense in patients with SAPS may be affected during high scaption [16], but seems to be preserved during axial humerus rotation [18,34].…”
Section: Joint Position Sensementioning
confidence: 61%
“…Two additional articles were retrieved from the reference lists of included studies. Thirteen full-text articles were excluded, resulting in 12 articles for the final analysis ( Figure 1) [16][17][18][27][28][29][30][31][32][33][34][35]. One study performed both a comparison of proprioception between patients with SAPS and controls and assessed the efficacy of an intervention in SAPS, and was therefore used for both study questions (Table 1) [32].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…O SPA é classificado como uma submodalidade da propriocepção que tem como função interpretar a informação sobre a posição e orientação no espaço (Myers et al, 2006). A literatura científica sobre propriocepção de indivíduos com SDS permanece inconclusiva, Sahin et al (2017) mostraram que indivíduos com SDS apresentam propriocepção alterada quando comparados a controles saudáveis (Sahin et al, 2017), enquanto Gomes et al (2019) mostraram que indivíduos com SDS não apresentaram déficits proprioceptivos quando comparados aos controles pareados (Gomes et al, 2019). Nosso estudo foi o primeiro a avaliar o SPA ativo em indivíduos com SDS utilizando uma ponteira laser e nossos resultaram apontaram uma diferença entre grupos apenas após exercício com barra flexível.…”
Section: Resultsunclassified